2020
DOI: 10.17265/2332-7839/2020.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile and Hepatic Enzymes Differences between Pre-diabetes and Normal Staff

Abstract: Purpose:The aim of this study was to investigate lipid profile and hepatic enzymes difference between pre-diabetes and normal subjects.Methods:In this cross-sectional study, 264 employees of Energy Industries Engineering & Design (EIED) Company were randomly selected and participated in the study in January 2019.A sample of 10 mL of venous blood was obtained between 8 a.m. and 10 a.m. Blood analyses for fasting glucose (FG), total cholesterol (TC), triglyceride (TG), LDL-cholesterol, HDL-cholesterol, aspartate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Extensive studies have shown that obesity increases the risk of chronic diseases, such as cancer, cardiovascular disease, stroke (the leading cause of death worldwide), diabetes and its complications, and musculoskeletal disorders (e.g. osteoarthritis) (2)(3)(4)(5). Type 2 diabetes (T2D) is a metabolic disease caused by a gradual decrease in insulin secretion or the inability of the body to respond to insulin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies have shown that obesity increases the risk of chronic diseases, such as cancer, cardiovascular disease, stroke (the leading cause of death worldwide), diabetes and its complications, and musculoskeletal disorders (e.g. osteoarthritis) (2)(3)(4)(5). Type 2 diabetes (T2D) is a metabolic disease caused by a gradual decrease in insulin secretion or the inability of the body to respond to insulin.…”
Section: Introductionmentioning
confidence: 99%
“…T2D was also responsible for 1.5 million direct deaths in 2019 (7). T2D is associated with various complications and disorders, such as vision problems (retinopathy), atherosclerosis, neurological diseases, kidney diseases (nephropathy), heart diseases, stroke, and finally death (5,8,9). The fat mass and obesity-associated (FTO) gene is associated with the development of obesity and related diseases.…”
Section: Introductionmentioning
confidence: 99%